Bank lending, financial frictions, and inside money creation - Lukas Altermatt (University of Zurich, Department of Economics, 2019)
I build a general equilibrium model of the transmission of monetary policy on bank lending. Bank lending is done by individual banks that face random investment opportunities by creating inside money. Banks are subject to a reserve requirement and have access to the interbank money market. The model shows that lowering the money market rate relative to the inflation rate reduces investment and welfare. This is because the money market is an outside option for banks that face bad investment opportunities. Reducing the money market rate lowers the value of this outside option, which in turn reduces banks' willingness to acquire reserves ex-ante. This leads to less aggregate reserves, which reduces the banking system's ability to grant credit.
Keywords: E4; E5; 330; monetary policy transmission; open market operations; channel system; interest rate pass-through